Development Model for the Development of Business Incubator Programs with a Technology Acceptance Model (TAM) Approach at the Cooperatives and SMEs Office of North Sumatra Province - Pasha, Raja Salsabila; Nasution, Harmein; Aritonang, Evawany Yunita (Universitas KH. Abdul Chalim Mojokerto, 2026)
Digital transformation is a strategic challenge for Micro, Small, and Medium Enterprises (MSMEs), especially in the context of technology readiness and acceptance. Although various coaching programs have been implemented by local governments, the results achieved by MSMEs show an uneven success rate. This research aims to develop a business incubator program development model based on the Technology Acceptance Model (TAM) at the Cooperatives and MSMEs Office of North Sumatra Province. The TAM approach is used to understand technology acceptance behavior through two main constructs, namely Perceived Usefulness (PU) and Perceived Ease of Use (PEOU), which are integrated with incubation programs and capital development. This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews with ten MSME actors participating in the 2024 business incubator program. The results of the study show that MSMEs feel the benefits of digital technology in increasing operational efficiency and expanding market reach. However, MSME actors still face obstacles in the application of production technology and limited access to formal financing. The incubation program is considered to be able to increase digital literacy, but it is not fully adaptive to the difference in the level of digital readiness of participants. Capital development is still informative and has not been accompanied by continuous technical assistance. This research resulted in a TAM based business incubator development model that places the perception of usefulness and convenience as the foundation for technology acceptance, and is strengthened by institutional support and a cross-agency coaching ecosystem. This model is expected to increase the effectiveness of MSME coaching in a more inclusive, adaptive, and sustainable manner.